The potential of sugar cane juice as the liquid supplement and phytase enzyme carrier for poultry by in vitro - Ermin Widjaja; T. Toharmat; D.A. Santoso; Sumiati .; M. Ridla; S. Iskandar (Jurnal Ilmu Ternak dan Veteriner, 2011)
Most of the components of poultry feed (80%) of grains and meal that contains phytic acid which has anti-nutritional factor because it can bind minerals and reduce its availability. Phytic acid can be hydrolyzed by the enzyme phytase. Phytase enzyme naturally found in sugar cane juice, but its use as poultry feed supplements have not been done. The study was conducted using sugar cane juice PS 851 from Jatiroto PTPN XI, Lumajang, East Java in order to get the information potential of sugar cane juice as a liquid supplement and phytase enzyme carrier for poultry viewed from the aspect of nutrient content of sugarcane juice and phytase activity in the release rate of phosphorus. Research conducted at the Faculty of Animal IPB for 10 months. The rate of hydrolysis of phytase on P was tested using rice bran as a substrate. Sugar cane juice is added to the 2.5% level, using 4-level incubation (1, 2, 3 and 4 hours), each level consisting of 37°C and 42°C; pH 2; pH 4.5 and pH 5 with three replications. Study using a Two Factors Experiments in Completely Randomized Design and it was continued by DMRT test. P release rate was measured by spectrophotometry. The results showed that the sugar cane juice has a phytase activity of 0.0766 U / ml, brix level of 22.15%, containing water 73.03%, protein 0.47%, crude fiber 6.43%, minerals Ca 0.03%, P 0,02%, Co 0.14 mg / l, Fe 1.8 mg/l, Mn 1.55 mg/l, Zn 1.37 mg/ l, Cu 0.19 mg/ l, Se 12.63 mcg/100 g, vitamins B3 5.26 mg/100 g, C 0.72 mg/100 g, E 0.08 mg/100 g, sucrose 32.42%, fructose 2.41%, galactose 2% and glucose 1.58%. Supplementation of 2.5% sugar cane juice can increase the P release rate of 112-235% at optimum conditions of pH 5, at 37°C with a long incubation period of 1-4 hours. Key Words: Sugar Cane Juice, Phytase, Phosphorus